The burning room [compact disc, unabridged] : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series., 2014)
Bosch and rookie Detective Lucia Soto, are tasked with solving what turns out to be a highly charged, politically sensitive case. Beginning with the bullet that's been lodged for years in the victim's spine, they must pull new leads from years-old information, which soon reveal that this shooting may have been anything but random.